COMMENSAL SMALL MAMMAL SPECIES AND BAIT PREFERENCES IN URBAN AREAS OF PENANG ISLAND - Amni, Wan Nur; Ravindran, Shakinah; Saufi, Safwan; Hamid, Noor Hisham; Zainal Abidin, Cik Mohd Rizuan; Ahmad, Abu Hassan; Salim, Hasber (Malaysian Journal of Science, 2019)
Physical trapping is an important first step in controlling pest populations and species identification; and bait preferences are crucial information for effective management. This study was conducted to explore species diversity and bait preferences of commensal species in urban areas on Penang Island. Live trapping was carried out in eight sampling sites on Penang Island in commercial and residential areas. Eight different type of baits were used; apple and peanut butter (APB), white bread and peanut butter (BPB), salted fish (SF), salted fish and peanut butter (SFPB), white bread and fish extract (BFE), fried chicken leftover (FCL), vegetables and peanut butter (VPB) and sausages (S). The most successful bait was the high protein bait, fried chicken leftover (FCL), with a capture success rate of 35.56%. We also analysed the bait preferences for the different species of small mammals captured in our study. Five species of small mammals were captured in our study sites: Rattus norvegicus, Rattus rattus, Mus musculus, Bandicota bengalensis and Suncus murinus. Norway rats, R. norvegicus was the most trapped species in commercial areas whereas lesser bandicoot rats, B. bengalensis was the most captured species in residential areas.